Ergonomia de tablets em uso ocupacional: atividade visual e biomecânica postural sob a influência de ofuscamentos reflexivos causados pela iluminação - Ribeiro, Alexandre de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
With the recent and successful implementation of the occupational use of the digital tablet in school and work environmentas. With the recent and successful implementation of the accupational use of the tablet in school and work enviornments, little attention has been palid to ergonomic principles in this process at the same time, in which several ergonomic problems have arisen. The approach of this research came from the hypothesis tha the ambience commonly found is not suitable for activities with videos terminals in the horizontal plane, or close to this. The interaction with the highly reflexive interface of the tablet tends to generate glare by reflection, wich can compromise the performance of the visual exploration activity, as well as lead to inappropriate postural compensations due to the searc for better visual condition. In this context, the objective was analyze the occupational use of the tablet how much the influence of glare by reflection about the performance of the visual exploration activity and postural biomechanics of the cervical region of the spine. The research was developed with 20 participants with a mean age of 20.2 years, who underwent the prescribed task of visual observation of optatypes and verbalization of their direction, subjected the areas with and without glare by reflection in the tablet interface. To the collect of data were used integrated systems of tracking of the eye and of the head, the first applied to the analysis of visual exploration activity, represented by the behavior of the live of the horizontal gaze and the second to measure the postural biomechanics of cervical spine by kinematics analysis of head movements (position - coordinates of the axes, X, Y and Z) and (orientation - angles of rotation, azimuth, elevation and roll). The data were treated at the Matlab and subjected to statistical analysis (ANOVA one-way for repeated measures) for the effect of glare, with three levels (before...

Atualmente, pesquisas sobre ergonomia relacionada à iluminação do ambiente não estão restritas à concepção qualitativa de condições visuais, vertentes apontam para a importância de considerar os impactos biológicos da interação com a luz. Com a recente e próspera implementação do uso ocupacional do tablet, em ambientes escolares e de trabalho, pouca atenção tem sido dada aos princípios ergonômicos neste processo, ao mesmo tempo, em que surgiram diversas problemáticas ergonômicas. A abordagem desta pesquisa surgiu da hipótese de que a ambiência luminosa comumente encontrada não é adequada para atividades com terminais de vídeo no plano horizontal, ou próximo deste. A interação com a interface altamente reflexiva do tablet tende a gerar ofuscamento por reflexão, o qual pode comprometer o desempenho da atividade de varredura visual, bem como levar a compensações posturais inadequadas em função da busca por uma melhor condição visual. Neste contexto, o objetivo foi analisar o uso ocupacional do tablet quando à influência do ofuscamento refletivo sobre o desempenho da atividade de varredura visual e biomecânica postural da região cervical da coluna vertebral. A pesquisa foi desenvolvida com 20 participantes, com idade média de 20,2 anos, quais realizaram tarefa prescrita de observação visual de optótipos e verbalização de sua direção, sujeitos a áreas com e sem ofuscamento refletido na interface do tablet. Para a coleta de dados foram utilizados sistemas eye tracker e head tracker integrados, o primeiro aplicado à análise da atividade de varredura visual, representa pelo comportamento da linha do olhar horizontal e o segundo para aferir a biomecânica postural da coluna cervical, por meio da análise cinemática dos movimentos da cabeça (posição - coordenadas nos eixos X, Y e Z) e (orientação - ângulos azimuth, elevation e roll). Os dados foram tratados no Matlab e submetidos à análise...
Keywords: Tablet; Ergonomia; Iluminação; Visão; Tablet computers